2011
DOI: 10.1016/j.bbr.2011.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of hypothalamic insulin receptor expression elicits depressive-like behaviors in rats

Abstract: Ongoing epidemiological studies estimate that greater than 60% of the adult US population may be categorized as either overweight or obese. There is a growing appreciation that the complications of obesity extend to the central nervous system (CNS) and may result in increased risk for neurological co-morbidities like depressive illness. One potential mechanistic mediator linking obesity and depressive illness is the adipocyte derived hormone leptin. We previously demonstrated that lentivirus-mediated downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 64 publications
(75 reference statements)
5
55
0
1
Order By: Relevance
“…phosphorylation of Akt and GSK3β. As it has been previously demonstrated, the impairment of insulin and/or leptin signaling due to inappropriate diet (e.g., HF diet) [33,34,37], or the under-expression of the insulin receptor [38] or leptin receptor [39] promotes depressive-like symptoms in rodents. Leptin receptor deletion in the hippocampus results in depressive-like behaviors in mice [39], while leptin treatment reduces depressive-like symptoms and inhibits hippocampal GSK3β via phosphorylation on Ser9 in rats [40].…”
Section: Discussionmentioning
confidence: 82%
“…phosphorylation of Akt and GSK3β. As it has been previously demonstrated, the impairment of insulin and/or leptin signaling due to inappropriate diet (e.g., HF diet) [33,34,37], or the under-expression of the insulin receptor [38] or leptin receptor [39] promotes depressive-like symptoms in rodents. Leptin receptor deletion in the hippocampus results in depressive-like behaviors in mice [39], while leptin treatment reduces depressive-like symptoms and inhibits hippocampal GSK3β via phosphorylation on Ser9 in rats [40].…”
Section: Discussionmentioning
confidence: 82%
“…This reduction was sufficient to suppress the brain lactate increase in the barrel cortex during whisker stimulation, to modify 13 C-SE lactate C3 and glutamate C4 as well as the ratios of different carbons in glutamate and glutamine. A 40% decrease in protein content was described previously to be sufficient to observe a clear phenotype in the case of other target proteins, suggesting that it is not necessary to achieve prominent suppression of protein expression to be able to obtain significant alterations in functional and/or metabolic responses [53,54]. However, it would be desirable to improve the efficiency of the viral vector approach in order to increase the reliability and extent of the effects observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, at this time it is not conclusive as to whether insulin resistance induces depression or the opposite. Although a study found that downregulation of hypothalamic insulin receptor expression elicits depressive-like behaviors in rats [21], others found that the occurrence of depression precede the onset of diabetes [22], and that insulin resistance can be reversed by antidepressant treatment [23]. Meanwhile, not only are depressive symptoms a risk factor for the development of T2D, they have also been shown to contribute to hyperglycemia, diabetic complications, functional disability and all-cause mortality among diabetic patients [4], [5].…”
Section: Discussionmentioning
confidence: 99%